2018
DOI: 10.1038/s41416-018-0025-x
|View full text |Cite
|
Sign up to set email alerts
|

DNMTi/HDACi combined epigenetic targeted treatment induces reprogramming of myeloma cells in the direction of normal plasma cells

Abstract: BackgroundMultiple myeloma (MM) is the second most common hematologic malignancy. Aberrant epigenetic modifications have been reported in MM and could be promising therapeutic targets. As response rates are overall limited but deep responses occur, it is important to identify those patients who could indeed benefit from epigenetic-targeted therapy.MethodsSince HDACi and DNMTi combination have potential therapeutic value in MM, we aimed to build a GEP-based score that could be useful to design future epigenetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 73 publications
0
24
0
Order By: Relevance
“…We have previously shown in human myeloma cell lines that this combination represses MYC transcriptional responses. 17 Similarly, MYC expression was downregulated in the murine 5T33vt cells upon treatment confirming the MYC-targeting effects of combining DNMTi and HDACi in MM (Supplementary Figure S1H). The combination effects were also observed with 100 nM DAC and 10 nM Quis which in the 4-day combination setup resulted in 70% Annexin-V positivity at day 6 and 80% at day 7 (Supplementary Figure S1I).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…We have previously shown in human myeloma cell lines that this combination represses MYC transcriptional responses. 17 Similarly, MYC expression was downregulated in the murine 5T33vt cells upon treatment confirming the MYC-targeting effects of combining DNMTi and HDACi in MM (Supplementary Figure S1H). The combination effects were also observed with 100 nM DAC and 10 nM Quis which in the 4-day combination setup resulted in 70% Annexin-V positivity at day 6 and 80% at day 7 (Supplementary Figure S1I).…”
Section: Resultsmentioning
confidence: 59%
“…In line with the above studies, we observed significant cytotoxic activity and MYC depletion of the combination of DAC and Quis in the murine MM cells in this study and in previous published studies in HMCLs. 17,22 …”
Section: Discussionmentioning
confidence: 99%
“…The prognostic value of proliferation assessment using BrdU incorporation was analyzed in 60 newly diagnosed patients treated with high dose chemotherapy supported by autologous hematopoietic stem cell transplantation (HSCT). Using R Maxstat algorithm , allowing to determine the optimal cutpoint for continuous variables , we identified that MM patients with a percentage of proliferating MMCs >1.42 are associated with a significant shorter event free survival (20 months median EFS) ( P = 0.0005) compared with patients with a percentage of proliferating MMCs ≤ 1.42 (not reached median EFS) (Fig. B).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in both our study ( Figure 6E-H) and others, the combination of DAC with HDAC inhibitors is more efficacious due to the synergistic deregulation of specific cell-survival genes. 65,[71][72][73] Precise mechanisms responsible for this synergy remain to be elucidated and are likely to involve numerous signaling molecules 63,65,71,73,74 and to be cell type dependent. Our model suggests that these antimyeloma therapies upregulate TAZ, leading to decreased MYC expression and its transcriptional program and subsequent cell death.…”
Section: Discussionmentioning
confidence: 99%